IMPLEMENTASI KARTU INDONESIA PINTAR DALAM MENINGKATKANIKUALITAS PENDIDIKANIDI DESA PURWASARI KECAMATAN CICURUG KABUPATENISUKABUMI - Muhamad Subkhan (Jurnal Dialektika Politik, 2023)
The main theory in this study is the theory of policy implementation according to Edward III in Agustino (2017: 136). This research uses a qualitative approach, where qualitative research is a research method that is shown to describe existing phenomena. The data collection in this study is based on reality in the field through observation, interviews and documentation. This study contained 6 informants as a key instrument of data collection consisting of the Village Head, Village Secretary, Village Social Welfare Center (Pukesos), KIP distribution officer in school, and 2 beneficiary communities in Purwasari Village. From the results of research that has been done shows that the Implementation of smart Indonesia Card Policy (KIP) in improving the quality in Purwasari Village, Cicurug District, Sukabumi Regency has not been effective because there are still some obstacles in its implementation, such as the validity of the data owned is not synchronized between the existing data and the data in the center, because the data is still using old data, in addition, there are still people who should get the KIP program but do not get it because of data collection that has not been in verval (validation and verification). Therefore, the Purwasari Village Government and related parties need to make efforts by coordinating, meaning that in data collection regarding the Smart Indonesia Card (KIP) program in Purwasari Village can be coordinated effectively between related implementing institutions, so as to reduce data that is not on target.